Responsible AI Growth with Safety: Exploring Global and National Policy Discourse - Chaturvedi, Sachin; Kumar, Amit (Journal of Information and Knowledge, 2024)
The extremely complex landscape of responsible Artificial Intelligence (AI) requires a multifaceted and integrated approach. That a framework for responsible AI cannot work in isolation and will require collaborations at the global level is emphasized. As AI systems must meet a high degree of safety standards, the importance of evolving safety guidelines in consultation with all the stakeholders is highlighted. Suggests the need for an international body in collaboration with other nations for the development, standardization and use of AI technology. Considering the sensitivity and far-reaching impact of AI across nations which defies borders, it is suggested that the Government of India should collaborate with international agencies and governments of other countries to form a global agency that will act as the primary international body for development, standardization and responsible use of AI.